Digital technologies in art education: problems, solutions - Goryacheva Elena (E3S Web of Conferences, 2022)
Digital technologies, which entered education at the beginning of the 21th century, are actively developing in connection with the prevailing conditions in society throughout the planet in 2020-2021. They have influenced both the education system in general and the artistic direction, especially in distance learning. The developments of scientists and teachers presented at the last congress of sociologists ROS and psychological and pedagogical concepts of humanistic, personality-oriented education contain a discussion of the existing digital space and proposals for the organization of digital education in higher education, including the artistic students' specialization. Based on this and the didactic concept of teaching, we continued the author's methods of optimizing the artistic activity of students in distance learning at a university, described in previous articles, reflecting its specificity, results of the application, and outlined prospects for this direction of creative activity that develops personality in modern conditions.